1997
DOI: 10.1103/physreve.55.455
|View full text |Cite
|
Sign up to set email alerts
|

Role of interfacial entropy in the command-surface effect

Abstract: The paper presents a study of the evolution of the tilt angle with time in ''command-surface'' liquid crystal cells under irradiation with UV light. In these cells, the liquid crystal orientation can be switched via a photoinduced isomerization of azo moieties attached to the surface. The trans and the cis state induce homeotropic and homogeneous alignment, respectively. Polymeric systems assembled with the Langmuir-Blodgett ͑LB͒ technique were employed. Not only homeotropic and homogeneous alignment, but also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
2
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 19 publications
0
23
2
1
Order By: Relevance
“…Büchel et al 17 showed, with an LB layer composed of a polyglutamate having an Az side group, that visible light irradiation induces the orientational change of LC molecule without a threshold. This is contradictory to the present observation.…”
Section: Comparison With Three-dimensional Lc Cell Systemmentioning
confidence: 98%
See 1 more Smart Citation
“…Büchel et al 17 showed, with an LB layer composed of a polyglutamate having an Az side group, that visible light irradiation induces the orientational change of LC molecule without a threshold. This is contradictory to the present observation.…”
Section: Comparison With Three-dimensional Lc Cell Systemmentioning
confidence: 98%
“…11,[14][15][16][17][18][19] The trans and cis forms of the surface Az layer generally induce homeotropic and homogeneous or planer alignment, respectively. In the same manner, the 6Az10-PVA/5CB hybrid LB films investigated here exhibit reversible changes in molecular tilt upon alternative UV and visible light irradiation.…”
Section: Validity Of Interface Modeling Of Command Surfacementioning
confidence: 99%
“…The induced alignment was also stable on further irradiation with 436 nm unpolarized light at the same incident angle, in contrast to the results reported in the literature, in which the tilt angle was controlled by the amount of exposure energy. [10,11] Removal of the induced alignment was easily achieved by irradiation with unpolarized light at 366 nm, where a photo-chemical phase transition occurs. [1] The alignment could be reinduced on irradiation with unpolarized light at 436 nm.…”
mentioning
confidence: 99%
“…[3,4] These processes coupled with isomeric configurations and conformations of the azobenzene have also been shown to play a crucial role in the observed photoinduced anchoring transitions of nematic LCs. [9,10] The pretilt angle is defined here as the angle between the surface and the average tilt direction of the LC director. [9,10] The pretilt angle is defined here as the angle between the surface and the average tilt direction of the LC director.…”
Section: Photocontrolled Alignment Of Chiral Nematic Liquid Crystalsmentioning
confidence: 99%